Bangladesh Economic Update, April 2011 - World Bank (Washington, DC, 2017)
The outlook for FY2011 has changed since the last macroeconomic update in October 2010.1 While gross development product (GDP) growths is still projected to be around 6.2 percent in FY11, inflationary pressures have strengthened and the external position has weakened. Rising energy and food subsidies are placing a strain on the budget, but higher-than-anticipated revenues and lower-than-budgeted Annual Development Program expenditures leave sufficient fiscal space for the government to react to these pressures. Progress on reforms is mixed, with advances made on Value Added Tax reforms, efforts to tighten liquidity and setting up a framework for public-private partnership projects. Developments on telecommunication policy, the Anticorruption Commission, and policy responses to stock market volatility are a cause for concern. The growth outlook for FY12 remains good but there are risks that need to be contained. Short-term risks include rising food and fuel prices, deteriorating remittances, an increased reserve drawdown, a growing quasi-fiscal deficit, stock market volatility and its potential impact on the banking sector. Long-term risks include the inability to sufficiently alleviate power shortages, raise public investment, and remove bottlenecks for private investment.